Emotional availability in women with bipolar disorder and major depression: A longitudinal pregnancy cohort study. (November 2021) - Aran, Pavitra; Lewis, Andrew J; Watson, Stuart J; Nguyen, Thinh; Galbally, Megan
Objective: Poorer mother–infant interaction quality has been identified among women with major depression; however, there is a dearth of research examining the impact of bipolar disorder. This study sought to compare mother–infant emotional availability at 6 months postpartum among women with perinatal major depressive disorder, bipolar disorder and no disorder (control). Methods: Data were obtained for 127 mother–infant dyads from an Australian pregnancy cohort. The Structured Clinical Interview for the DSM -5 was used to diagnose major depressive disorder ( n = 60) and bipolar disorder ( n = 12) in early pregnancy (less than 20 weeks) and review diagnosis at 6 months postpartum. Prenatal and postnatal depressive symptoms were measured using the Edinburgh Postnatal Depression Scale, along with self-report psychotropic medication use. Mother and infant's interaction quality was measured using the Emotional Availability Scales when infants reached 6 months of age. Multivariate analyses of covariance examining the effects of major depressive disorder and bipolar disorder on maternal emotional availability (sensitivity, structuring, non-intrusiveness, non-hostility) and child emotional availability (responsiveness, involvement) were conducted. Results: After controlling for maternal age and postpartum depressive symptoms, perinatal disorder (major depressive disorder, bipolar disorder) accounted for 17% of the variance in maternal and child emotional availability combined. Compared to women with major depressive disorder and their infants, women with bipolar disorder and their infants displayed lower ratings across all maternal and child emotional availability qualities, with the greatest mean difference seen in non-intrusiveness scores. Conclusions: Findings suggest that perinatal bipolar disorder may be associated with additional risk, beyond major depressive disorder alone, to a mother and her offspring's emotional availability at 6 months postpartum, particularly in maternal intrusiveness.